Studies of the extracytoplasmic function sigma factor PG0162 in Porphyromonas gingivalis - Dou, Yuetan (Mol Oral Microbiol, 2015)
PG0162, annotated as an extracytoplasmic function (ECF) sigma factor in Porphyromonas gingivalis, is composed of 193 amino acids. As previously reported, the PG0162-deficient mutant, P. gingivalis FLL350 showed significant reduction in gingipain activity compared to the parental strain. Because this ECF sigma factor could be involved in the virulence regulation in P. gingivalis, its genetic properties were further characterized. A 5’-RACE analysis showed that the start of transcription of the PG0162 gene occurred from a guanine (G) residue 69 nucleotides upstream of the ATG translation initiation codon. The function of PG0162 as a sigma factor was confirmed in a run-off in vitro transcription assay using the purified rPG0162 and RNAP core enzyme from E.coli with the PG0162 promoter as template. Since an appropriate PG0162 inducing environmental signal is unknown, a strain overexpressing the PG0162 gene designated P. gingivalis FLL391 was created. Compared to the wild-type strain, transcriptome analysis of P. gingivalis FLL391 showed that approximately 24% of the genome displayed altered gene expression (260 upregulated genes; 286 downregulated genes). Two other ECF sigma factors (PG0985 and PG1660) were upregulated more than 2 fold. The autoregulation of PG0162 was confirmed with the binding of the rPG0162 protein to the PG0162 promoter in electrophoretic mobility shift assay. In addition, the rPG0162 protein also showed the ability to bind to the promoter region of two genes (PG0521 and PG1167) that were most upregulated in P. gingivalis FLL391. Taken together, our data suggest that PG0162 is a sigma factor that may play an important role in the virulence regulatory network in P. gingivalis.